Evaluation on control efficacy of Parthenium hysterophorus L. through chemical approaches - Hasan, Mahmudul; Masilamany, Dilipkumar; Ruzmi, Rabiatuladawiyah; Motmainna, Mst.; Ahmad Hamdani, Muhammad Saiful (Sociedade Brasileira da Ciencia das Plantas Daninha, 2024)
Background: Parthenium hysterophorus L. is a globally significant invasive weed causing numerous negative impacts. Several pre-and post-emergence herbicides are available, but information on the control efficacy against Parthenium in Malaysia is limited. Objective: Therefore, a series of experiments were conducted in laboratory, glasshouse, and field conditions to evaluate the efficacy of selected pre-and post-emergence herbicides to control Parthenium. Methods: Pre-emergence herbicides imazethapyr, indaziflam, pretilachlor, sodium chloride, diuron, atrazine, and metsulfuron-methyl were applied in the lab (Petri dish seed bioassay) and under different soil moisture conditions (field capacity, flooded and saturated) in a glasshouse trial. Post-emergence herbicides (glyphosate-isopropylamine, glufosinate-ammonium, 2,4-D, propanil, bentazone+MCPA, and metsulfuron-methyl) were applied in the glasshouse and field conditions. Results: In the seed bioassay, no seed germination was recorded in all applied dosages of imazethapyr, indaziflam, pretilachlor, and sodium chloride. Parthenium weed was totally controlled by all applied herbicides in field capacity condition, but lower efficacy was observed for sodium chloride (97.50%), imazethapyr (92.50%), and pretilachlor (86.25%) in saturated condition. In the post-emergence herbicides dose-response experiment, glufosinate-ammonium, 2,4-D, and bentazone+MCPA fully controlled (100%) Parthenium but slightly lower control (97–98%) was observed by glyphosate-isopropylamine, propanil, and metsulfuron-methyl. In the field trial, all the applied herbicides showed 100% mortality in both locations (Infoternak Farm and Kampung Tampin Linggi) except for metsulfuron-methyl (96.67% and 93.33%, respectively), although a higher rate (1.5x recommended rate) of glyphosate-isopropylamine was required to achieve the desired result. Conclusions: This study provides valuable information on suitable chemical control options for Parthenium weed in Malaysia.